2011
DOI: 10.1080/00480169.2011.547162
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the myth of the irrational dairy farmer; understanding decision-making related to herd health

Abstract: Veterinarians working with dairy cows are suggested to refocus their efforts from being task-oriented providers of single-cow therapy and develop themselves into advice-oriented herd health management advisors. The practising cattle veterinarian's ability to translate knowledge into on-farm application requires a profound understanding of the dairy farm as an integrated system. Consequently, educating and motivating farmers are key issues. To achieve such insight the veterinarian needs to work with several sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 48 publications
7
95
0
2
Order By: Relevance
“…When the impression of the identity of the farmer does not agree with the impression of the veterinary advisor there might be an increased risk that the communication between them is not effective. According to Kristensen and Jakobsen (2011), it is very important that the advisor communicates in a way that facilitates the context bound reality at individual farms and that they address the farmers' fundamental values in life. They recommend veterinary advisors to learn about the herd dynamics before defining advise and to provide necessary and sufficient information to support the provided advise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the impression of the identity of the farmer does not agree with the impression of the veterinary advisor there might be an increased risk that the communication between them is not effective. According to Kristensen and Jakobsen (2011), it is very important that the advisor communicates in a way that facilitates the context bound reality at individual farms and that they address the farmers' fundamental values in life. They recommend veterinary advisors to learn about the herd dynamics before defining advise and to provide necessary and sufficient information to support the provided advise.…”
Section: Discussionmentioning
confidence: 99%
“…The background of this approach was that previous studies showed that a "one-fits-all" communication does not work in stimulating the farmer to implement improvements (Kristensen and Jakobsen, 2011;Valeeva et al, 2007) and that tailored advice is needed. Thus both, veterinary and sociological aspects were combined in the given advise (tailored advise).…”
Section: Tailored Advisementioning
confidence: 98%
“…Previous work has recognised that the ability to come up with solutions for complex problems can benefit from integrating between several analytical approaches and knowledge generated by different scientific disciplines (Kristensen andJakobsen 2011, Wentholt, Cardoen et al 2012). Studies from participatory epidemiology have highlighted the importance of capturing and including farmers' understandings of disease in scientific analyses of disease transmission (Catley, Alders et al 2012, Leach andScoones 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with previous research showing that the veterinarian is being perceived as a highly trusted and influential referent in herd health management (e.g. Ellis-Iversen et al, 2010;Kristensen and Jakobsen, 2011;Lam et al, 2011;Derks et al, 2013;Fisher, 2013). This suggests that for future BT alike vaccination strategies, the social interactions between veterinarians and farmers might be an appropriate communication channel to use.…”
Section: Discussionsupporting
confidence: 80%